Brain Tumors - Analysis of 320 Cases - Rahman, Md Lutfor; Ali, ASM Shawakat; Islam, Md Shofiqul; Alam, Intekhab; Mohiuddin, AKM (TAJ: Journal of Teachers Association, 2011)
We have studied 320 cases of brain tumour. In adults 80% tumours were supra-tentorial and 20% were infra-tentorial. In case of children, 71.25% were infra-tentorial and 29.8 % were supratentorial. Age ranges in our study were between 10 months to 75 years. Male to female ratio of incidence were about 2:1. All (100%) patients had cognitive impairment with features of raised intracranial pressure. Diagnosis was made on the basis of CT scan of brain (78.12%) or MRI of Brain (21.88%). Surgical intervention was done in the form of burr hole and biopsy in 45 cases (14.06%), Craniotomy with total excisional biopsy in 109 cases (34.6%) and excision and biopsy with residual tumors in 166 cases (51.81%). Peri-operative mortality in our study was 6.25%. doi: 10.3329/taj.v19i1.3164 TAJ 2006; 19(1): 24-26